The B Vitamins Nicotinamide (B3) and Riboflavin (B2) Stimulate Metamorphosis in Larvae of the DepositFeeding Polychaete Capitella teleta: Implications for a Sensory Ligand-Gated Ion Channel. - Pechenik, Jan A.; Burns, Robert T.; Biggers, William J.; Scavo, Gia.; Lehman, Christopher. (Tufts University. Tisch Library., 2017)
Marine sediments can contain B vitamins, presumably incorporated from settled, decaying phytoplankton and microorganisms associated with decomposition. Because B vitamins may be advantageous for the energetically intensive processes of metamorphosis, post-metamorphic growth, and reproduction, we tested several B vitamins to determine if they would stimulate larvae of the deposit-feeding polychaete Capitella teleta to settle and metamorphose. Nicotinamide and riboflavin individually stimulated larvae of C. teleta to settle and metamorphose, generally within 1-2 hours at nicotinamide concentrations as low as 3 µM and riboflavin concentrations as low as 50 µM. More than 80% of the larvae metamorphosed within 30 minutes at a nicotinamide concentration of 7 µM. The pyridine channel agonist pyrazinecarboxamide also stimulated metamorphosis at very low concentrations. In contrast, neither lumichrome, thiamine HCl, pyridoxine HCl, nor vitamin B12 stimulated larvae of C. teleta to metamorphose at concentrations as high as 500 µM. Larvae also did not metamorphose in response to either nicotinamide or pyrazinecarboxamide in calcium-free seawater or with the addition of 4-acetylpyridine, a competitive inhibitor of the pyridine receptor. Together, these results suggest that larvae of C. teleta are responding to nicotinamide and riboflavin via a chemosensory pyridine receptor similar to that previously reported to be present on crayfish chela and involved with food recognition. Our data are the first to implicate B vitamins as possible natural chemical settlement cues for marine invertebrate larvae.